Indoor positioning system for manufacturing and logistics - Teo, Kok Chun (Nanyang Technological University, 2024)
Research on Indoor Positioning System (IPS) and DWM1001 capabilities and finding ways to enhance warehouse IPS to track assets and try to apply a tag as an anchor to reduce the number of anchors needed in the environment. Being able to track the assets and visualise where are the asset moving in real time to reduce the amount of accident in warehouse and reduce the amount of time find to find assets or good in the warehouse.